Aligning Provider Prescribing With Guidelines for Soft Tissue Infections. Issue 3 (March 2022) - Kovaleski, Christopher; Courter, Joshua D.; Ghulam, Enas; Hagedorn, Philip A.; Haslam, David B.; Kurowski, Eileen Murtagh; Rudloff, James; Szczesniak, Rhonda; Dexheimer, Judith W.
Abstract : Objective: Despite evidence-based guidelines, antibiotics prescribed for uncomplicated skin and soft tissue infections can involve inappropriate microbial coverage. Our aim was to evaluate the appropriateness of antibiotic prescribing practices for mild nonpurulent cellulitis in a pediatric tertiary academic medical center over a 1-year period. Methods: Eligible patients treated in the emergency department or urgent care settings for mild nonpurulent cellulitis from January 2017 to December 2017 were identified by an International Classification of Diseases, Tenth Revision, code for cellulitis. The primary outcome was appropriateness of prescribed antibiotics as delineated by adherence with the Infectious Diseases Society of America guidelines. Secondary outcomes include reutilization rate as defined by revisit to the emergency department/urgent cares within 14 days of the initial encounter. Results: A total of 967 encounters were evaluated with 60.0% overall having guideline-adherent care. Common reasons for nonadherence included inappropriate coverage of MRSA with clindamycin (n = 217, 56.1%) and single-agent coverage with sulfamethoxazole-trimethoprim (n = 129, 33.3%). There were 29 revisits within 14 days of initial patient encounters or a reutilization rate of 3.0%, which was not significantly associated with the Infectious Diseases Society of America adherence. Conclusions: Our data show antibiotic prescription for nonpurulent cellulitis as a potential area of standardization and optimization of care at our center.